The Differentiation of Modernism : Postwar German Media Arts - Powell, Larson (Studies in German literature, linguistics, and culture., 2014)
The Differentiation of Modernism analyzes the phenomenon of intermediality in German radio plays, film music, and electronic music of the late modernist period (1945-1980).